Effects of digestate solid fraction fertilisation on yield and soil carbon dioxide emission in a horticulture succession - Maucieri, Carmelo; Nicoletto, Carlo; Caruso, Caterina; Sambo, Paolo; Borin, Maurizio (Italian Journal of Agronomy, 2017)
The aim of this study was to evaluate the agronomical and environmental effects of digestate solid fraction (DSF) used as fertiliser in a vegetable crop succession (green bean, savoy cabbage, cabbage and cauliflower) in Northeast Italy (45°20’ N; 11°57’ E). Three fertilisation treatments were tested using DSF to substitute 0% (Tmin), 50% (T50) and 100% (T100) optimal level of mineral nitrogen fertilisation. The experiment was carried out from 22nd May 2014 (green bean sowing) to 3rd June 2015 (cabbage harvest). Summer and spring crops did not show significantly different marketable yield among fertilisation treatments with an average value (±standard error) of 9.0±0.5, 9.9±1.2 and 51.3±6.4 Mg ha–1 for green bean, cauliflower and cabbage, respectively. Lower DSF fertilisation effect was monitored on winter crop (savoy cabbage) with a marketable yield reduction of -35.1% than mineral fertilisation (25.9 Mg ha–1), whereas the T50 treatment was not significantly different compared to the two previous ones. Crop species significantly influenced the N use efficiencies with negative recovery and use efficiency indexes for the DSF fertilisation treatments. Soil CO2 emissions were not significantly influenced by fertilisation in all studied crops with median values always lower than 1 g m–2 h–1.